The Triumph of Islamic Education in the Bani Abbasiyah State and Its Influence on Education in the Digital Era - Zaenal Arifin; Atsqbit, Aqid; Sutowo, Shahaby; Nurlathifah, Nailah; Aulia, Chanda; Muaffa, Aulia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Islamic education began to develop since the time of the Prophet Muhammad, the Khulafaur Rasyidin, the Umayyads, and the Abbasids, and continues to develop until now. Islamic education developed, especially during the Abbasid Dynasty. The purpose of this article is to discuss the concept of Islamic education during the Abbasid dynasty and the current development of Islam. This study uses a descriptive qualitative approach. Information for this study was obtained from various sources, including print and online media, as well as from various other sources. The results of this study indicate that Islamic educational institutions during the Abbasid dynasty can be categorized into three categories. consisting of formal educational institutions, such as madrasahs, non-formal educational institutions, such as mosques, kutabs, bookstores, and libraries, and informal educational institutions, such as the homes of scholars. The number of educational institutions shows that this is in accordance with the belief in Islam which requires seeking knowledge and is considered a form of worship